2021
DOI: 10.1107/s1600577520013958
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Percival detector with soft X-rays

Abstract: In this paper the back-side-illuminated Percival 2-Megapixel (P2M) detector is presented, along with its characterization by means of optical and X-ray photons. For the first time, the response of the system to soft X-rays (250 eV to 1 keV) is presented. The main performance parameters of the first detector are measured, assessing the capabilities in terms of noise, dynamic range and single-photon discrimination capability. Present limitations and coming improvements are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It has been shown that these sensors dramatically increase the full-frame acquisition speed (48 Hz for the standard gain and 24 Hz for the HDR mode) compared to the commercial Back-Side-Illuminated Charge-Coupled Device (CCD-BSI) routinely used at soft X-ray facilities. The first utilization of this device opened up perspectives for soft X-ray ptychography (Mille et al, 2022), soft X-ray scattering techniques (Desjardins et al, 2020;Marras et al, 2021) and other applications, such as soft X-ray fluorescence (Staeck et al, 2021). Another obvious application concerns the implementation of such a class of detectors at ultra-short X-ray sources (laser-based X-ray source or free-electron laser), where the low frame rate of the standard commercially available CCD-BSI (see, for example, Vodungbo et al, 2012;Wang et al, 2012) limits the time of data collection.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that these sensors dramatically increase the full-frame acquisition speed (48 Hz for the standard gain and 24 Hz for the HDR mode) compared to the commercial Back-Side-Illuminated Charge-Coupled Device (CCD-BSI) routinely used at soft X-ray facilities. The first utilization of this device opened up perspectives for soft X-ray ptychography (Mille et al, 2022), soft X-ray scattering techniques (Desjardins et al, 2020;Marras et al, 2021) and other applications, such as soft X-ray fluorescence (Staeck et al, 2021). Another obvious application concerns the implementation of such a class of detectors at ultra-short X-ray sources (laser-based X-ray source or free-electron laser), where the low frame rate of the standard commercially available CCD-BSI (see, for example, Vodungbo et al, 2012;Wang et al, 2012) limits the time of data collection.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Section 1, the PERCIVAL system is in its final development phase. Its capabilities at the time of the experiments in summer/fall 2020 have already been described elsewhere (Marras et al, 2021). The larger dynamic range of the PERCIVAL sensor, and its large active area compared with other detectors, permit the user to register much higher q values, carrying more high-frequency information, which is key to achieve higher spatial resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity of ptychography to variations of the sample thickness is independent of the treatment energy and defined by the refractive index of the sample. The spatial resolution of the ptychography technique is determined by the highest scattering angle detected [50]. Moreover, the sensitivity of ptychography can be further increased by switching to a reflective geometry, potentially achieving sub-nm profile sensitivity with nm spatial resolution [51,52].…”
Section: Discussionmentioning
confidence: 99%